Implementation of Flipped Classroom as Student-Centered Learning Implementation in Awatara Learning of 7 Grade At SMP Negeri Satap 2 Kintamani - Ni Nyoman Sriasih Ratnawati (International Journal of Multidisciplinary Sciences, 2023)
Talking about learning and teaching certainly cannot be separated from how skilled an educator is in developing learning strategies. This also applies to all subjects taught, one of which is Hinduism. Learning Hinduism aims to build morals and virtuous behavior through the guidelines of the holy book, namely the Vedas, so this causes many educators in the field of Hinduism to only focus on conveying teachings from the Vedic scriptures, especially the story of Avatar by delivering material through the lecture method. without paying attention to the interests of their students. Even though in this era of globalization, children are often easily influenced by foreign cultures so interest in exploring their own beliefs is reduced, and each student has a variety of learning styles. The ability of educators to design learning strategies greatly influences students' interest in Hinduism lessons and students can internalize and deepen the moral values that are learned through the learning process they go through, one of which is by implementing flipped classrooms as an implementation of student-centered learning in Avatara learning for learning experiences which is more meaningful. This research is qualitative in nature with data collection methods in the form of participant observation. The results obtained are that through the flipped classroom students can train their creative thinking skills well and can create innovations based on moral values obtained from Avatara learning. The conclusion from this study is that flipped classes can be a solution to teaching strategies for learning Avatara material as the application of student learning centered for a meaningful learning process amid the demands of teachers who must understand the diverse student learning styles.